Trends and Dynamics of Literature about Working Capital Management Published in 2000-2024 - Judijanto, Loso (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric analysis of the literature on Working Capital Management (WCM) published between 2000 and 2024. Drawing data from the Scopus database and employing VOSviewer for visualization, the research maps the intellectual structure, thematic evolution, and collaborative networks within the field. The analysis reveals that WCM research has expanded from a focus on profitability and liquidity toward more interdisciplinary concerns, including knowledge management, human capital, social capital, and sustainability. Co-citation and keyword co-occurrence networks identify three major thematic clusters: traditional financial efficiency, strategic-financial integration, and behavioral-organizational perspectives. Temporal overlays indicate that emerging themes such as psychological capital, leadership, and sustainability have gained prominence in recent years. Additionally, the country collaboration network highlights the global nature of WCM research, with active contributions from both developed and emerging economies. This study not only synthesizes two decades of scholarly development in WCM but also provides insights for future research directions that integrate finance with strategy, technology, and organizational behavior.